In Eastern Ghats of India Gliricidia sepium is beneficial for resource conservation and plant nutrient supply - Dass, Anchal; Sudhishri, Susama; Choudhury, P. R.; Lenka, N. K. (Indian Farming, 2016)
Gliricidia is a leguminous tree which produces nutrient rich and easily decomposable biomass upto 20 t/ha and offers an alternate source of plant nutrients, particularly in eastern ghats region of India where a large segment of population is poor and cannot afford costly synthetic fertilizers. This short height tree can be planted on field bunds or within fields as hedgerows, and its leaves can be harnessed as green leaf manures in situ/ex-situ. Studies conducted on Gliricidia clearly demonstrated its potential of biomass (leaves and twigs) as a reliable source of nutrients, to be integrated with the INM schedule of crops, such as finger millet, upland rice, low land rice and vegetable crops. When planted as hedgerow, it reduced the runoff, soil and nutrient losses tremendously.